Recommendations for Improving the ISO 14001 Certification Based on the Company's Perception Analysis of the Certification Obstacles and Benefits - Noviana Bayu Alnavis; Dwi Nowo Martono; Udi Syahnoedi Hamzah (Universitas Airlangga, 2021)
Introduction: Environmental management systems (EMS) were used commonly by companies to control industrial impacts and support environmental sustainability. In achieving SDG's indicators to focuses on improving sustainable practices in the company environment, the government faces a tough challenge in increasing ISO 14001 certified companies. This study aimed to analyze the barriers and benefits of ISO 14001 certification in the industrial sector and recommend encouraging companies to carry out ISO 14001 certification. Methods: This study used a descriptive analysis method to identify the perception of ISO 14001 certified company practitioners of the certification barriers and benefits. Through survey questionnaires, data collection was conducted to 83 ISO14001 certified companies with a response rate of 49.4%. Results and Discussion: The main barrier in performing the ISO 14001 was the cost of implementation and certification. The highest benefit of ISO 14001 certification was to improve the company's image. A total of 83% of the companies believed that the benefits of ISO 14001 certification outweighed the costs incurred. Conclusion: The companies did not have significant barriers in conducting the ISO 14001 certification and classified into the medium category. The ISO 14001 certification could provide environmental sustainability, social, market, and economic benefits. The government needs to support the interest of companies in conducting the ISO 14001 implementation by overcoming the obstacles and maximizing the benefits.